Fabaceae Lindl. in the Patos and Sousa-Cajazeiras Semiarid Intermediate Geographical Regions in Paraíba State, Brazil - Pereira, Alessandro Soares; Sousa, Emanuel Evaristo De; Queiroz, Rubens Teixeira De; Pereira, Maria Do Socorro (Phytotaxa, 2026)
We present here a floristic survey of the Fabaceae family in the Patos and Sousa-Cajazeiras Intermediate Geographic Regions (RGINTs), historically known as Sertão and Alto Sertão, in Paraíba State, Brazil. The study was conducted between February/2022 and February/2025, based on literature reviews, consultations of the SpeciesLink and Virtual Herbarium of Flora and Funga (Reflora) online databases, and the analysis of specimens deposited in 35 national and three international herbaria. A total of 260 species were recorded, distributed among 78 genera, with the subfamily Caesalpinioideae (131 species, 31 genera) being the most representative, followed by Papilionoideae (112 species, 43 genera), Detarioideae (9 species, 3 genera), and Cercidoideae (8 species, monospecific). Of the 260 species recorded, 52 are endemic to Brazil and 28 are exclusive to the Caatinga domain. Of the taxa encountered in the study area, 78 species represent new occurrences for the flora of Paraíba, and approximately 40% of them are classified on the Red List as threatened or endangered species of the Brazilian flora. This study contributes to the expansion of our floristic knowledge of the Caatinga vegetation of Paraíba State, Brazil, and provides subsidies for their preservation and sustainable management of their remnants.